A Note to Consilience Readers - Wilson, E. O. (Consilience, 2008)
The last decade of events around the world have brought into clearer focus than ever before this overarching principle: humanity’s many troubles will not abate, they will grow steadily worse, unless humanity can agree on the lodestar of sustainable development. We find ourselves in the early steep climb of exponential change: per capita consumption of materials and energy; the demand for shrinking natural resources, most critical of which is fresh water; climate change with an impact on virtually every aspect of human welfare; the cost of war; and the destruction of ecosystems and species, which have hitherto sustained us scot free. These trends are interlocked and mutually reinforcing. We must study and address them as a unity. Success would ensure a future for humanitarian civilization. Failure is unthinkable.